Preparation and Activity of Precipitated Ni-MgO/Al2O3 Catalysts for the Partial Oxidation of Methane - Luis F Razon; Carlito M Salazar; Hiroo Niiyama; Long The Nam Doan (ASEAN Journal of Chemical Engineering, 2007)
The effect of catalyst preparation methods, NiO/MgO molar ratio and reaction temperature on the performance of Ni-MgO catalysts supported on Al2O3 in the partial oxidation of methane to syngas were investigated in a fixed-bed flow reactor. Three catalyst preparation methods (all slight variants of the precipitation method) produced comparable results in CH4 conversion, CO and H2 selectivities. Energy Dispersive X-Ray (EDX) analysis and the color of the catalysts after reaction showed that catalysts produced by simultaneous dissolution of the nickel and magnesium salts may have better carbon deposition resistance. NiO/MgO molar ratio significantly affected the performance of the catalyst. When the NiO/MgO ratio decreased, activity decreased. At a NiO/MgO molar ratio of 1/2 and a reduction temperature of 850°C, CH4 conversion and CO selectivity increased when reaction temperature increased while H2 selectivity remained almost the same. The catalyst gave excellent activity and remained stable after 5h time-on-stream.